Processing Papaya Fruit into Snacks as a Food Security Innovation in Mandiku Hamlet, Sidodadi Village - Andi Dwi Sandi Hariyono; Aulavia Hidayaturrobbani; Shinta Mayasari (Sean Institute, 2026)
Dusun Mandiku in the village of Sidodadi is an area with abundant agricultural potential. One of the most commonly found agricultural products in this hamlet is papaya. Papaya plants have high economic value because they have many uses, from the roots, leaves, fruit, stems, to the flowers. The objective of this research is to develop an innovation in papaya processing into a snack, which not only benefits the economic value of papaya but also serves as a concrete step in supporting village food security. The research method employed a descriptive qualitative approach. The research results also show that this papaya processing innovation brings several important benefits. First, from an economic perspective, the community gains additional income from the sale of processed products. Papayas that were previously unsold or discarded can now generate income. Second, from a social perspective, this activity involves housewives, fostering unity, cooperation, and enhancing family self-reliance. Third, from a food safety perspective, papaya snacks can be stored longer than fresh papaya, making them a food reserve when needed.